METODE DAKWAH USTADZ ANDRI MALIN BATUAH DALAM MEMBINA KARAKTER GENERASI MUDA DI MASJID JAMI’ SUMANIK KABUPATEN TANAH DATAR - Mirardhi Nuzul Fajar; Tomi Hendra (Adisam Publisher, 2025)
The Da'wah method is a method used by a preacher to convey Islamic teachings to the congregation with the aim of inviting them to goodness and truth in accordance with the guidance of the Qur'an and Sunnah. The background of this research is based on the successful da'wah delivery process of Ustadz Andri Malin Batuah in developing the character of the younger generation in the mosque to avoid various delinquent behaviors such as stealing, adultery/dating, and bullying. This method utilizes an appropriate approach or method so that the da'wah message is conveyed and well-received by the congregation. This study aims to determine and analyze Ustadz Andri Malin Batuah's da'wah method in developing the character of the younger generation at the Sumanik Grand Mosque in Tanah Datar Regency. This study uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The primary informant was Ustadz Andri Malin Batuah, and supporting informants included the village head of Sumanik, two mosque administrators, two religious leaders, six mosque youth, and two parents of teenagers.The results of the study indicate that the da'wah methods used by Ustadz Andri to foster the character of the younger generation are: first, al-hikmah (Islamic teachings) delivered wisely, openly, and with compassion toward teenagers through activities such as wirid (recitation of Islamic teachings) for teenagers via virtual videos. Second, al-mauizah hasanah (Islamic teachings) is delivered in the form of lectures, with activities such as self-reflection for teenagers, including advice, guidance, discussion, and motivation. The challenges faced by Ustadz Andri Malin Batuah in da'wah include the influence of social media and popular culture, the lack of interest and encouragement among teenagers in participating in religious activities, the lack of participation and support from community leaders, and the inability of teenagers to understand religion deeply.